Rotation sequences for the calculation of shoulder kinematics of the volleyball attack - Barrett, K. B.; Parrish, K.; Bennett, H. J. (Journal of Biomechanics, 2023)
Calculating upper extremity kinematics during overhead movements presents with problems typically not seen for the lower extremity due to the large range of motion. Due to these unique issues, different rotation sequences have been suggested to circumvent challenges due to gimbal lock (GL) and angle coherence (AC). The purpose of this study is to determine the most appropriate rotation sequence for shoulder angle calculation during a volleyball attack. METHODS: 15 healthy experienced volleyball players (women = 8) performed 5 attacks off a stationary ball. A 12-camera 3D motion capture system was utilized to record trunk and arm kinematics to compare joint angles calculated using the YXY, ZXY, XZY, YXZ, ZYX, and XYZ rotation sequences. Instances of GL and AC inconsistences were marked for each trial. The last 3 trials were used for analysis. RESULTS: The YXY and XYZ sequences presented with the least total number of errors (12 and 5, respectively). 5 instances of GL were present in the XYZ sequence while none were recorded for the YXY sequence. All other sequences returned incoherent angles that greatly exceeded known ranges of motion. CONCLUSION: When performing kinematic analyses during a volleyball attack, researchers should adhere to ISB recommendations and employ the Eulerian YXY sequence for calculations. If greater anatomical understanding is desired, the XYZ sequence may be utilized for most subjects.